Answer: The sum of the lengths of any two sides of a triangle must be greater than the length of the third side. Since, 11 + 21 > 16, 11 + 16 > 21, and 16 + 21 > 11, you can form a triangle with side lengths 11 mm, 21 mm, and 16 mm.
Step-by-step explanation:
Answer:
![\huge\boxed{x=-4}](https://tex.z-dn.net/?f=%5Chuge%5Cboxed%7Bx%3D-4%7D)
Step-by-step explanation:
![3(x+9)-4x=11x-13x+23\\\\(3)(x)+(3)(9)-4x=(11x-13x)+23\\\\3x+27-4x=-2x+23\\\\(3x-4x)+27=-2x+23\\\\-x+27=-2x+23\qquad|\text{subtrsact 27 from both sides}\\\\-x=-2x-4\qquad|\text{add}\ 2x\ \text{to both sides}\\\\x=-4](https://tex.z-dn.net/?f=3%28x%2B9%29-4x%3D11x-13x%2B23%5C%5C%5C%5C%283%29%28x%29%2B%283%29%289%29-4x%3D%2811x-13x%29%2B23%5C%5C%5C%5C3x%2B27-4x%3D-2x%2B23%5C%5C%5C%5C%283x-4x%29%2B27%3D-2x%2B23%5C%5C%5C%5C-x%2B27%3D-2x%2B23%5Cqquad%7C%5Ctext%7Bsubtrsact%2027%20from%20both%20sides%7D%5C%5C%5C%5C-x%3D-2x-4%5Cqquad%7C%5Ctext%7Badd%7D%5C%202x%5C%20%5Ctext%7Bto%20both%20sides%7D%5C%5C%5C%5Cx%3D-4)
ANSWER
![{i}^{31} = - i](https://tex.z-dn.net/?f=%20%7Bi%7D%5E%7B31%7D%20%20%3D%20%20-%20i)
EXPLANATION
We want to evaluate
![{i}^{31}](https://tex.z-dn.net/?f=%20%7Bi%7D%5E%7B31%7D%20)
Use indices to rewrite the expression as:
![= {i}^{30} \times i](https://tex.z-dn.net/?f=%20%3D%20%20%7Bi%7D%5E%7B30%7D%20%20%5Ctimes%20i)
We know that
![{i}^{2} = - 1](https://tex.z-dn.net/?f=%20%7Bi%7D%5E%7B2%7D%20%20%3D%20%20-%201)
So we rewrite the expression to obtain;
![= ({ {i}^{2}) }^{15} \times i](https://tex.z-dn.net/?f=%20%3D%20%20%28%7B%20%7Bi%7D%5E%7B2%7D%29%20%7D%5E%7B15%7D%20%20%5Ctimes%20i)
This gives us;
![= {( - 1) }^{15} \times i](https://tex.z-dn.net/?f=%3D%20%20%20%7B%28%20-%201%29%20%7D%5E%7B15%7D%20%20%5Ctimes%20i)
This simplifies to
![= - 1 \times i](https://tex.z-dn.net/?f=%20%3D%20%20-%201%20%5Ctimes%20i)
![= - i](https://tex.z-dn.net/?f=%20%3D%20%20-%20i)
<span> 7x+2y=5;13x+14y=-1 </span>Solution :<span><span> {x,y} = {1,-1}</span>
</span>System of Linear Equations entered :<span><span> [1] 7x + 2y = 5
</span><span> [2] 13x + 14y = -1
</span></span>Graphic Representation of the Equations :<span> 2y + 7x = 5 14y + 13x = -1
</span>Solve by Substitution :
// Solve equation [2] for the variable y
<span> [2] 14y = -13x - 1
[2] y = -13x/14 - 1/14</span>
// Plug this in for variable y in equation [1]
<span><span> [1] 7x + 2•(-13x/14-1/14) = 5
</span><span> [1] 36x/7 = 36/7
</span><span> [1] 36x = 36
</span></span>
// Solve equation [1] for the variable x
<span><span> [1] 36x = 36</span>
<span> [1] x = 1</span> </span>
// By now we know this much :
<span><span> x = 1</span>
<span> y = -13x/14-1/14</span></span>
<span>// Use the x value to solve for y
</span>
<span> y = -(13/14)(1)-1/14 = -1 </span>Solution :<span><span> {x,y} = {1,-1}</span>
<span>
Processing ends successfully</span></span>
Answer:
3. f(12) = -10; f(37) = -60
4. f(12) = -102; f(37) = -352
Step-by-step explanation:
3. Put the numbers in the formula and do the arithmetic:
f(12) = 12 -2(12-1) = 12 -22 = -10
f(37) = 12 -2(37-1) = 12 -72 = -60
__
4. The explicit formula for an arithmetic sequence with first term a1 and common difference d is ...
an = a1 +d(n -1)
Your sequence has a first term a1=8 and a common difference d=-10.
As above, fill in the numbers and do the arithmetic.
f(12) = 8 -10(12 -1) = -102
f(37) = 8 -10(37-1) = -352